Efficacy and safety of the first-in-class imidazoline-2 receptor ligand CR4056 in pain from knee osteoarthritis and disease phenotypes: a randomized, double-blind, placebo-controlled phase 2 trial. Issue 1 (January 2020) - Rovati, L.C.; Brambilla, N.; Blicharski, T.; Connell, J.; Vitalini, C.; Bonazzi, A.; Giacovelli, G.; Girolami, F.; D'Amato, M.
Summary: Objective: CR4056 is a selective imidazoline-2 (I2) receptor ligand with potent analgesic activity in animal pain models. This proof-of-concept study tested CR4056 efficacy and safety in patients with knee osteoarthritis (OA) and different phenotypes. Design: This is a multicenter, randomized, double-blind, placebo-controlled trial. Knee OA patients with moderate to severe pain received CR4056 (women 100 mg bid; men 200 mg bid) or placebo (both genders) for 14 days. The primary outcome was the change in WOMAC pain score (0–100 scale) compared to placebo, analyzed in the intention-to-treat population and pre-defined OA phenotypes. Results: 213 patients were treated with CR4056 (92 women; 52 men) or placebo (69 overall). After 14 days, median WOMAC pain improvements were 10 points on placebo and 14, 20 and 16 in women, men, and pooled CR4056 groups ( P = 0.184, 0.030 and 0.070 vs placebo, respectively). Pre-specified subgroup analysis in the metabolic OA phenotype (BMI ≥ 27.5 kg/m 2, N = 156) showed statistically significant differences in all CR4056-treated groups vs placebo of 12–18 points. Conversely, there were too few patients with a neuropathic or inflammatory phenotype for a meaningful analysis. CR4056 was well tolerated; the most common adverse event was mild headache. Conclusions: Although the primary endpoint was met in males only, this exploratory phase 2 trial shows that CR4056 might be an effective analgesic against knee OA pain, especially in overweight patients representing the metabolic OA phenotype. These findings, along with the broad-spectrum analgesic activity of CR4056 in animal models, warrant further clinical investigation in OA and other pain conditions. Clinical trial registration number: EudraCT 2015-001136-37.